A projected conjugate gradient method for structural stability analysis with linear constraints - Jeusette, Jean-Pierre; Sonzogni, Victorio (Computers & structures, 1989)
In this paper a new iterative method to solve an eigenvalue problem subject to linear homogeneous inequality constraints is presented. This approach allows study of the linearized equilibrium path stability of a structure submitted to unilateral contact conditions. The solution is obtained by using a projected conjugate gradient technique to minimize the finite element discretized form of the Rayleigh quotient. The good behaviour of this algorithm is illustrated by some simple applications in structural mechanics.